Design features of the rotary endodontic instruments system ProFile (Эндодонтия Today)
Design features of the endodontic instrument determine its essential properties. Information about these design features carries inference about instrument properties and makes possible a comparative analysis of instruments with different design. The aim of the present work is a quantitative study and analysis of the Pro-File instruments design features. Thirty instruments of different size and taper have been included in this study. SEM examination of all instruments and their cross-sections was made to determine the following design parameters: tip angle, fluting angle, pitch length, fluting depth, internal and external diameters and the angles of cutting blade. Design features analysis of the ProFile instruments allows pointing out its outstanding characteristics: 1) high flexibility; 2) high cyclic fatigue resistance; 3) the ability to preserve the original root canal anatomy; 4) low cutting ability; 5) substantial screwing-in effect of the instruments of greater sizes.